“Factors of the Revisit Intention of Patients in the Primary Health Care System in Argentina“ - Pighin, Massimo (2022)
“The Argentine health system has three subsectors: private, social works, and public. It is essential to consider the user’s perceptions through studies that measure the intention to revisit, through self-perceived care quality, to obtain results from the health care process and adjust the services provided accordingly. A correlational, cross-sectional, and non-experimental study has been carried out. A total of 407 people were surveyed using a self-administered questionnaire with a five-point Likert scale. The model considered four variables: quality of the use of health programs, satisfaction, confidence, and revisit intention. Second-generation statistics were adopted through multivariate evaluation using partial least squares structural equation modeling (PLS-SEM) to calculate the correlation values between the study variables. The direct route between the quality of health services and satisfaction was not statistically significant, while the direct routes traced between the other constructs were statistically significant. This study contributes significantly to understanding how users determine the intention to re-choose a health service, explaining the indirect routes through which the quality of care relates to the intention to revisit.“